2015
DOI: 10.1111/inr.12185
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian mothers' knowledge of infants' childrearing and developmental milestones

Abstract: Healthcare professionals, nursing schools and healthcare policy makers are encouraged to develop and institute a holistic approach encompassing physical, cognitive, emotional and parent-infant interaction domains in childrearing educational programmes. Structured parenting programmes for mothers and culturally accepted sources of information for fathers are essential to enhance parenting skills among Jordanian couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 30 publications
8
27
4
2
Order By: Relevance
“…The results revealed that most of the mothers were knowledgeable about physical care activities but has limited awareness in cognitive care field, implied by the finding of a poor mean knowledge of Cognitive development in this study. This is in concordant with Jordanian study by Safadi et al (2015).…”
Section: Knowledge Of Cognitive and Vision Developmentsupporting
confidence: 93%
See 1 more Smart Citation
“…The results revealed that most of the mothers were knowledgeable about physical care activities but has limited awareness in cognitive care field, implied by the finding of a poor mean knowledge of Cognitive development in this study. This is in concordant with Jordanian study by Safadi et al (2015).…”
Section: Knowledge Of Cognitive and Vision Developmentsupporting
confidence: 93%
“…Regarding parity, there was a significant association between mother's knowledge on developmental milestone of children in motor, hearing and language fields and the number of delivered babies, which was different from study done in 2015 were no significant association was found (Safadi et al, 2015).…”
Section: Association Between Mother Knowledge Regarding Developmentalcontrasting
confidence: 86%
“…suspicion of a developmental problem in their children, because parents have an effective role in detection and prevention and early intervention. Safadi et al (2016) found that mothers were more knowledgeable in safety, physical skills and less in emotional, parent-infant interaction, and cognitive skills. Parental education, age-parity and planned pregnancy had limited impact on milestones of development of knowledge.…”
Section: In Relation To Hypothesis 2(f)mentioning
confidence: 94%
“…A study by Safadi et al (2016) aimed to detect Jordanian mothers" knowledge of child rearing exercises and milestones of development, the socio-demographic relevance to knowledge variables, and the information source that guide childrearing exercises. They use a design that is cross-sectional with a modified version of MacPhee"s "Knowledge of Infant Development Inventory" to evaluate 400 mothers" knowledge of infants" childrearing and milestones of development, in Amman, Jordan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 26 27 ] Jordanian mothers had more information about physical and safety abilities and less in cognitive, emotional, and parent–infant interaction abilities. [ 28 ]…”
Section: Introductionmentioning
confidence: 99%